Factors associated with stress, anxiety, and depression during social distancing in Brazil - Alex Sandro Rolland Souza; Gustavo Fonseca Albuquerque Souza; Gabriela Albuquerque Souza; Ana Lorena Nascimento Cordeiro; Gabriella Almeida Figueredo Praciano; Adricia Cristine de Souza Alves; Alan Chaves dos Santos; José Roberto Silva Junior; Manuela Barbosa Rodrigues Souza (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To estimate the prevalence of clinical signs and symptoms of severe/extreme stress, anxiety, and depression, as well as their associated factors, among Brazilians during social distancing. METHODS This is a cross-sectional study conducted in April/May 2020 with 3,200 Brazilians over 18 years old. Respondents' sociodemographic and clinical data were collected using an online questionnaire, which also included the 21-item Depression, Anxiety and Stress Scale (DASS-21) to assess emotional symptoms. Unadjusted and adjusted prevalence ratios and their respective 95% confidence intervals were estimated using Poisson regression models with robust variance. RESULTS Our results show the prevalence of severe/extreme stress was 21.5%, anxiety 19.4%, and depression 21.5%. In the final model, sociodemographic, clinical, and Covid-19-related factors were associated with severe/extreme stress, anxiety, and depression in Brazilians during social distancing due to the Covid-19 pandemic. We found the main factors associated with severe/extreme depression to be young women, brown, single, not religious, sedentary, presenting reduced leisure activities, history of anxiety and depression, increased medication use, and Covid-19 symptoms. CONCLUSION This study may help develop and systematically plan measures aimed to prevent, early identify, and properly manage clinical signs and symptoms of stress, anxiety, and depression during the Covid-19 pandemic.